2014
DOI: 10.1007/s10803-014-2298-0
|View full text |Cite
|
Sign up to set email alerts
|

Non-traumatic Dental Condition-Related Emergency Department Visits and Associated Costs for Children and Adults with Autism Spectrum Disorders

Abstract: We analyzed 2010 U.S. National Emergency Department Sample data and ran regression models to test the hypotheses that individuals with ASD are more likely to have non-traumatic dental condition (NTDC)-related emergency department (ED) visits and to incur greater costs for these visits than those without ASD. There were nearly 2.3 million NTDC-related ED visits in 2010. Less than 1.0% (children) and 2.1% (adults) of all ED visits were for NTDC. There was no significant difference in NTDC-related ED visits or co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 47 publications
(46 reference statements)
0
16
0
1
Order By: Relevance
“…In United States‐based studies, individuals with less education were more likely to use the ED for NTDCs compared to the more educated 17,33 . A North Carolina study found that fewer years of maternal education was associated with increased likelihood of NTDC ED visits among children participating in the Women Infants and Children (WIC) program 49 . In a Canadian survey assessing NTDC ED use among adults, education was not significantly associated with NTDC ED use 34 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In United States‐based studies, individuals with less education were more likely to use the ED for NTDCs compared to the more educated 17,33 . A North Carolina study found that fewer years of maternal education was associated with increased likelihood of NTDC ED visits among children participating in the Women Infants and Children (WIC) program 49 . In a Canadian survey assessing NTDC ED use among adults, education was not significantly associated with NTDC ED use 34 …”
Section: Resultsmentioning
confidence: 99%
“…ED use for NTDCs increased with lower levels of median community income and higher levels of unemployment. 23,24,45,56,49,52 Measures such as county Medicaid population and county uninsured population were not associated with ED use for NTDCs. 21,57 One study reported that not-for-profit hospitals had higher rates of NTDC ED visits compared to privately owned hospitals.…”
Section: Other Enabling Factorsmentioning
confidence: 92%
See 2 more Smart Citations
“…The international literature provides several reports that separate studies based on traumatic and nontraumatic dental emergencies [36][37][38][39], but not a single Brazilian study used this division, probably because of the differences between the organization of health services, since a large share of these articles refer to care in outpatient clinics and some involve care provided by a medical professional. Nonetheless, there was an analysis of traumatic events that corroborated the greater frequency of trauma in men and younger boys [40].…”
Section: Discussionmentioning
confidence: 99%